Iron-mediated cleavage of C-C bonds in vicinal tricarbonyl compounds in water. - Mecinović, J; Hamed, R; Schofield, C (2009)
Three of a kind: Vicinal tricarbonyl compounds undergo C-C cleavage mediated by ferric ions (see scheme). The observed cleavage of ninhydrin and dehydroascorbic acid has relevance for amino acid detection and the metabolism of vitamin C.